A QoS-enabled resource management scheme for F-HMIPv6 micro mobility approach - Lopes, Nuno Vasco (2013)
In the near future, wireless networks will certainly run real-time applications with special Quality of Service (QoS) requirements. In this context micro mobility management schemes such as Fast Handovers over Hierarchical Mobile IPv6 (F-HMIPv6) will be a useful tool in reducing Mobile IPv6 (MIPv6) handover disruption and thereby to improve delay and losses. However, F-HMIPv6 alone does not support QoS requirements for real-time applications. Therefore, in order to accomplish this goal, a novel resource management scheme for the Differentiated Services (DiffServ) QoS model is proposed to be used as an add-on to F-HMIPv6. The new resource management scheme combines the F-HMIPv6 functionalities with the DiffServ QoS model and with network congestion control and dynamic reallocation mechanisms in order to accommodate different QoS traffic requirements. This new scheme based on a Measurement-Based Admission Control (MBAC) algorithm is effective, simple, scalable and avoids the well known traditional resource reservation issues such as state maintenance, signaling overhead and processing load. By means of the admission evaluation of new flows and handover flows, it is able to provide the desired QoS requirements for new flows while preserving the QoS of existing ones. The evaluated results show that all QoS metrics analyzed were significantly improved with the new architecture indicating that it is able to provide a highly predictive QoS support to F-HMIPv6.